Advanced materials and manufacturing technology III special topic volume with invited peer reviewed papers only - Guo, Hun; Wang, Taiyong; Wang, Zijing; Wang, Hongfeng; Xu, Ji (Key engineering materials, 2018)
This special topics volume includes the peer-reviewed articles covering research and development in the area of the materials processing technologies in the mechanical engineering. This collection will be interesting and useful for many engineers, academics and also for students.